Reframing Creative Teaching in Secondary Music Teacher Education - Sabine Chatelain; Karine Barman; Carlos Lage-Gómez; Marcelle Moor (MDPI AG, 2024)
According to research about creativity in education, creativity can be considered an ability that can be fostered through specific teaching strategies. Consequently, future secondary music teachers should be equipped with the knowledge to develop students' musical creativity. A challenge for teacher training lies in providing concepts and strategies to develop this professional knowledge. With the aim of improving a music didactics course, the purpose of this study was to understand how student teachers' conceptions of creative music teaching evolved over one semester. In reference to the concept of creative teaching developed by Beghetto and research about the role of the teacher's body in music education, a specific framework to identify aspects of creative pedagogical knowledge was conceived. A thematic analysis of two semi-structured interviews with five future secondary music teachers provided a detailed picture of the evolution of their conceptions about creative music teaching. Interestingly, student teachers' knowledge of theoretical concepts presented in the course, as well as knowledge about the role of the body in creative music teaching, remained mainly implicit. Knowledge about their professional identities as creative musicians and pedagogues appeared to be relevant for enhancing awareness of how to teach with creativity. In order to describe this dimension more precisely, we develop the concept of creative stance knowledge as an emerging category from the data. Its potential for teacher training will be discussed, including a more embodied vision of creative pedagogical knowledge for music teacher training.